2014
DOI: 10.5713/ajas.2013.13422
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of <italic>PPARγ</italic>, <italic>FASN</italic>, and <italic>ACADM</italic> Genes in Various Adipose Tissues and <italic>Longissimus dorsi</italic> Muscle from Yanbian Yellow Cattle and Yan Yellow Cattle

Abstract: The objective of this study was to investigate the correlation between cattle breeds and deposit of adipose tissues in different positions and the gene expressions of peroxisome proliferator-activated receptor gamma (PPARγ), fatty acid synthase (FASN), and Acyl-CoA dehydrogenase (ACADM), which are associated with lipid metabolism and are valuable for understanding the physiology in fat depot and meat quality. Yanbian yellow cattle and Yan yellow cattle reared under the same conditions display different fat pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Differential expressions of FASN in muscle were reported within the same breed divergent for IMF content (in pig; Lim et al., ) and meat tenderness (in cattle; Zhao, Tian, et al., ; in pig; Zhao, Li, et al., ). Breed‐specific expression of FASN was also observed in pigs (Duran‐Montge, Theil, Lauridsen, & Esteve‐Garcia, ), cattle (Ji et al., ), and chicken (Cui et al., ). Consistent with previous studies performed by Ponsuksili, Murani, Walz, Schwerin, and Wimmers () and Miao et al.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Differential expressions of FASN in muscle were reported within the same breed divergent for IMF content (in pig; Lim et al., ) and meat tenderness (in cattle; Zhao, Tian, et al., ; in pig; Zhao, Li, et al., ). Breed‐specific expression of FASN was also observed in pigs (Duran‐Montge, Theil, Lauridsen, & Esteve‐Garcia, ), cattle (Ji et al., ), and chicken (Cui et al., ). Consistent with previous studies performed by Ponsuksili, Murani, Walz, Schwerin, and Wimmers () and Miao et al.…”
Section: Discussionmentioning
confidence: 92%
“…Differential expressions of FASN in muscle were reported within the same breed divergent for IMF content (in pig; Lim et al, 2017) and meat tenderness (in cattle; Zhao, Tian, et al, 2012;in pig;Zhao, Li, et al, 2012). Breed-specific expression of FASN was also observed in pigs (Duran-Montge, Theil, Lauridsen, & Esteve-Garcia, 2009), cattle (Ji et al, 2014), and chicken (Cui et al, 2012). Consistent with previous studies performed by Ponsuksili, Murani, Walz, Schwerin, and Wimmers (2007) and Miao et al (2010) on pigs differing in fatness traits, which revealed that the expression of FASN was up-regulated in the fatter pig breed than in the leaner breed, our present study identified significantly increased expression of FASN in both the liver and the breast muscle in male SQ squabs characterized with significantly higher IMF content.…”
Section: Variability Of Expression Levels Of Genes In Relation To Imfmentioning
confidence: 92%
“…This would be consistent with the results obtained here, where, aside from the mammary gland, higher levels of expression of FASN were only seen in the subcutaneous fat. High levels of FASN gene expression have previously been reported in lactating and non-lactating buffalo ( B. bubalis ) mammary gland and subcutaneous fat tissue [28], although in humans, FASN was reported to be expressed in all tissues studied, with the highest levels observed in the liver and lungs [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In cumulus cells of the PAPP‐A treatment group, AGPAT9 , FASN , EGFR , HAS2 , and IMPDH1 were downregulated, whereas VNN1 was upregulated. Regarding genes related to lipid metabolism, AGPAT9 participates in triacylglycerol synthesis and membrane‐lipid biosynthesis (Körbes, Kulcheski, Margis, Margis‐Pinheiro, & Turchetto‐Zolet, ; Zeng et al, ), whereas the FASN gene is involved in long fatty acid biosynthesis (Ji et al, ; Yang, Cappello, & Wang, ). IGF‐1 plays an important role in the development and differentiation of white and brown adipose tissue (Blüher, Kratzsch, & Kiess, ; Sudano et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…participates in triacylglycerol synthesis and membrane-lipid biosynthesis (Körbes, Kulcheski, Margis, Margis-Pinheiro, & Turchetto-Zolet, 2016;Zeng et al, 2017), whereas the FASN gene is involved in long fatty acid biosynthesis (Ji et al, 2014;Yang, Cappello, & Wang, 2015).…”
Section: Groupsmentioning
confidence: 99%